Potential of a native araticum species as the rootstock of atemoya cultivars propagated by grafting methods (Acta Scientiarum. Agronomy, 2023)
Technical and secure information on the production of quality atemoya seedlings (Annona squamosa L. x Annona cherimola Mill.) are of paramount importance due to the growing interest in this crop. This study aimed to assess the formation of atemoya seedlings propagated by grafting methods and cultivars using araticum (Annona sylvatica) rootstocks. The experiment was carried out in a screened environment at the Western Paraná State University (Unioeste), Campus of Marechal Cândido Rondon, Paraná State, Brazil. Atemoya grafts (Thompson, African Pride, and Gefner) were collected from plants from the CATI seedling nursery, located in São Bento do Sapucaí, São Paulo State, Brazil. Grafting was performed using 1-year-old araticum rootstocks with 8–10 mm in diameter at a height of 15 cm from the ground and grafts measuring, on average, 8.5 cm in length, 10 mm in diameter, and three buds. The experimental design consisted of randomized blocks in a 3 Ã— 3 factorial arrangement (three grafting methods: cleft graft, whip and tongue graft, and chip budding Ã— three cultivars: African Pride, Thompson, and Gefner), with four replications and 10 seedlings per replication, totaling 40 seedlings per treatment. The percentage of graft success (%), percentage of sprouting (%), number of sprouts, number of leaves, and longest sprout length (cm) were assessed at 60 days after grafting. The cleft graft method is efficient for producing atemoya seedlings. The cultivar African Pride can be grafted onto rootstocks by the cleft graft and whip and tongue graft methods, as they promote a higher percentage of graft success. The Annona sylvatica rootstock has potential for the production of atemoya seedlings, but chip budding is not viable.